2014
DOI: 10.1021/ja507372v
|View full text |Cite
|
Sign up to set email alerts
|

Poly(oligoethylene glycol methacrylate) Dip-Coating: Turning Cellulose Paper into a Protein-Repellent Platform for Biosensors

Abstract: The passivation of nonspecific protein adsorption to paper is a major barrier to the use of paper as a platform for microfluidic bioassays. Herein we describe a simple, scalable protocol based on adsorption and cross-linking of poly(oligoethylene glycol methacrylate) (POEGMA) derivatives that reduces nonspecific adsorption of a range of proteins to filter paper by at least 1 order of magnitude without significantly changing the fiber morphology or paper macroporosity. A lateral-flow test strip coated with POEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…1e ), a notable benefit for optimizing the sensitivity of any bioassay. This degree of protein repellency is consistent with our previous work on sequential dip-coating of POA/POH on cellulose paper; 33 however, the printing method is both significantly faster (seconds as opposed to hours 33 ) and enables localized gel printing essential for creating microarrays. This method allows for a covalently crosslinked hydrogel to be printed in the absence of ultraviolet (UV) photopolymerization to facilitate gelation 43 , avoiding the need for a secondary processing step as well as eliminating the potential for enzyme denaturation sometimes observed because of the radical species generated during polymerization 44 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1e ), a notable benefit for optimizing the sensitivity of any bioassay. This degree of protein repellency is consistent with our previous work on sequential dip-coating of POA/POH on cellulose paper; 33 however, the printing method is both significantly faster (seconds as opposed to hours 33 ) and enables localized gel printing essential for creating microarrays. This method allows for a covalently crosslinked hydrogel to be printed in the absence of ultraviolet (UV) photopolymerization to facilitate gelation 43 , avoiding the need for a secondary processing step as well as eliminating the potential for enzyme denaturation sometimes observed because of the radical species generated during polymerization 44 .…”
Section: Resultssupporting
confidence: 88%
“…Interfacial thin-film hydrogels are particularly attractive since they can minimize the kinetic/diffusional drawbacks associated with bulk hydrogels in biosensing applications, promoting fast assay speeds 31 while maintaining the benefits of size selectivity 32 . Several methods have been developed to fabricate thin-layer interfacial hydrogels on various substrates, including dip-coating 33 , spray deposition 34 , spin-coating 35 , and drop-on demand printing 36 . Printing is particularly advantageous since it is amenable to dispensing small volumes (minimizing sample volumes for screening), can localize materials in specific patterns (enabling, for example, facile printing of multisample arrays on a substrate), and can be scaled to commercial production 37 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we tested the versatility of this strategy for functionalization of PVC by graft polymerization of other methacrylate monomers, where PFMA, a widely used and efficient building block for postfunctionalization, [41][42][43] and OEGMA, a popular monomer for the preparation of antifouling materials, 44,45 were used as examples (entries 7 and 8 in Table 1) for the polymerization under similar conditions. We also observed the formation of PVC-g-PPFMA and PVCg-POEGMA graft copolymers with narrow molecular weight distributions (M w /M n ≤ 1.29) ( Fig.…”
Section: Graft Copolymerization Of Methacrylate Monomers In the Absenmentioning
confidence: 99%
“…Ma et al [7] first reported that a 15-nm thick P9 brush grown directly from the surface of gold displayed very low protein adsorption. Since this report, a number of additional inorganic solids, including silicon(1 0 0), gold, mesoporous silica, silicon oxide, cellulose paper, etc., have been protected with pOEGMA brushes [55][56][57][58][59][60][61][62][63]. In a systematic evaluation of the molecular parameters of pOEGMA influencing non-fouling, Ma et al [25] made the interesting observation that the conformation of the main-chain changed from a collapsed to an extended state above a certain main-chain length.…”
Section: Shielding Of Bulk Solidsmentioning
confidence: 99%